Maireinfra 2023 2023
DOI: 10.3390/engproc2023036048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Road Traffic Vibration on Micro-Dynamic Response of Precision Instrument Vibration Isolation Platforms

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…An experimental study was conducted to evaluate the influence of heavy-vehicle-induced vibration on precision instruments, which found that the amplitude of heavy vehicles is about 3~5 times that of small cars [35]. Another study focused on the attenuation of ground-borne vibrations by applying isolation measures for sensitive areas with precision instruments [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study was conducted to evaluate the influence of heavy-vehicle-induced vibration on precision instruments, which found that the amplitude of heavy vehicles is about 3~5 times that of small cars [35]. Another study focused on the attenuation of ground-borne vibrations by applying isolation measures for sensitive areas with precision instruments [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Fang at el. proposed precision instrument vibration isolation platforms intended to manage horizontal road vibrations during vehicle operation and validated their accuracy using on-site measurement results [22].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical component referred to as a 'vibration isolator' or 'mount module' fulfills the role of maintaining the supporting system at a desired height while simultaneously preventing the transmission of vibrational energy generated during operation [1][2][3][4][5][6][7][8][9][10][11]. Within the operational processes of each subcomponent, the mount module tries to mitigate the interference among adjacent subcomponents to the greatest possible extent and minimizes the reactive forces generated during operation, thereby favorably securing the desired dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%